2013
DOI: 10.2147/opth.s45351
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral corticosteroids followed by early surgical resection of large amblyogenic eyelid hemangiomas in infants

Abstract: BackgroundThe purpose of this study was to evaluate the results and complications of early surgical resection of large amblyogenic subdermal eyelid hemangiomas in infants after prior short-term parenteral administration of corticosteroids.MethodsSixteen infants were given dexamethasone 2 mg/kg/day in two divided doses for three consecutive days prior to scheduled surgical excision of large eyelid hemangiomas. The lesions were accessed via an upper eyelid crease, subeyebrow incision, or a lower eyelid subciliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Most HMs disappear without treatment, leaving minimal or no visible marks. Surgical removal is sometimes indicated, particularly if there has been delay in commencing treatment and if structural changes have become irreversible (Essawy & Galal, 2013). Until recently, the mainstay of treatments include the systematic use of corticosteroids (Nieuwenhuis, de Laat, Janmohamed, Madern, & Oranje, 2013) and beta-blockers (Petrovic et al, 2017), the intralesional injection of corticosteroid (Chantharatanapiboon, 2008; Prasetyono & Djoenaedi, 2011) and antitumor drugs (Hou, Wang, Tang, Wang, & Huang, 2011;Wang et al, 2009), the topical use of betablockers (Mashiah et al, 2017;Schneider, Reimer, Cremer, & Ruef, 2014;Wang et al, 2017) and 5% imiquimod (Ho, Lansang, & Pope, 2007;Ma et al, 2011;Welsh, Olazar an, G omez, Salas, & Berman, 2004), and lasers (Li, Hu, Li, & Deng, 2016;Ying et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most HMs disappear without treatment, leaving minimal or no visible marks. Surgical removal is sometimes indicated, particularly if there has been delay in commencing treatment and if structural changes have become irreversible (Essawy & Galal, 2013). Until recently, the mainstay of treatments include the systematic use of corticosteroids (Nieuwenhuis, de Laat, Janmohamed, Madern, & Oranje, 2013) and beta-blockers (Petrovic et al, 2017), the intralesional injection of corticosteroid (Chantharatanapiboon, 2008; Prasetyono & Djoenaedi, 2011) and antitumor drugs (Hou, Wang, Tang, Wang, & Huang, 2011;Wang et al, 2009), the topical use of betablockers (Mashiah et al, 2017;Schneider, Reimer, Cremer, & Ruef, 2014;Wang et al, 2017) and 5% imiquimod (Ho, Lansang, & Pope, 2007;Ma et al, 2011;Welsh, Olazar an, G omez, Salas, & Berman, 2004), and lasers (Li, Hu, Li, & Deng, 2016;Ying et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the mainstay of treatments include the systematic use of corticosteroids (Nieuwenhuis, de Laat, Janmohamed, Madern, & Oranje, 2013) and beta-blockers (Petrovic et al, 2017), the intralesional injection of corticosteroid (Chantharatanapiboon, 2008;Prasetyono & Djoenaedi, 2011) and antitumor drugs (Hou, Wang, Tang, Wang, & Huang, 2011;Wang et al, 2009), the topical use of betablockers (Mashiah et al, 2017;Schneider, Reimer, Cremer, & Ruef, 2014;Wang et al, 2017) and 5% imiquimod (Ho, Lansang, & Pope, 2007;Ma et al, 2011;Welsh, Olazar an, G omez, Salas, & Berman, 2004), and lasers (Li, Hu, Li, & Deng, 2016;Ying et al, 2017). Surgical removal is sometimes indicated, particularly if there has been delay in commencing treatment and if structural changes have become irreversible (Essawy & Galal, 2013). It has been reported that sclerotherapy with ethanol (Muto, Kinehara, Takahara, & Sato, 1990;Szejnfeld et al, 2015), sodium tetradecyl sulfate (Damodaran, McAuliffe, Wong, McCloskey, & Lee, 2012), and polidocanol (lauromacrogol 400; Winter, Dräger, & Sterry, 2000) is an easy, safe, and effective modality for localized lesions.…”
Section: Introductionmentioning
confidence: 99%